Genetic structure of the population of Pseudocercospora ulei in the watershed of the Amazon river - Santos, Taciana Ferreira (2018)
South American leaf blight (SALB) is a destructive disease caused by the fungus Pseudocercospora ulei that can severely affect rubber tree in monoculture in tropical America. The causal agent of the disease is a hemibiotrophic pathogen, that grows slowly under in vitro conditions. Isolation of good quality DNA in proper quantities is not an easy task due to the difficulties in the handling of P. ulei under laboratory conditions and the lack of a standard protocol. Although SALB has been known for nearly a century, information on the genetic structure of P. ulei in the Amazon region, its center of origin, remains unknown. In this work, adequate protocols for DNA extraction were assessed and the population genetic structure of P. ulei in the Amazon region was determined using 12 microsatellite loci (SSR). Six extraction protocols were compared regarding yield and purity of the DNA. A total of 61 isolates were sampled along the Madeira, Purus and Juruá watersheds located in the Amazon region and SSR genotyped. The Doyle and Doyle DNA extraction protocol was the one that presented consistent and better quality extracted DNA. There was linkage disequilibrium between alleles and genetic differentiation between geographically distant populations was detected. Principal component analysis revealed clustering of the isolates according to the watershed boundaries. Two groups were formed, one comprised by individuals from the Madeira river and the other comprised of individuals from the Purus and Juruá rivers.